Mengapa Kita Percaya Skincare Berlapis? Membaca Diskursus Multi-step Skincare di Media Sosial - Salma Prasantika Amada; Diah Kusumawati (Universitas Sebelas Maret (UNS), 2026)
Social media has significanly influenced modern beauty standards, particularly through the trend of complex skincare routines. This study investigates how the local beauty brand Somethinc, construct and normalizes the discourse of multi-step skincare through its Instagram account @somethincofficial. Using Norman Fairclough’s Critical Discourse Analysis (CDA), this qualitative research analyzes 20 selected Instagram post from 2020 to 2025 and includes interviews with the brand’s production team. The results reveal that Somethinc constructs a specific standard of beauty defined as “glowing” and “healthy”, which requires a disciplined, multi-layered skincare regime. At the textual level, the brand combines scientific visual with casual language to make this routine feel necessary. At the level of discursive practice, the brand solidifies its authority through Instagram itself, integrated cross-platform distribution, influencer endorsements, and paid ads at Meta Ads. At the social cultural level, Somethinc’s discourse shifts the concept of “self-love” into “consumptive feminism”, where caring for oneself is equated with purchasing products. The study concludes that these skincare trends are note merely educational but are ideological tools that align personal care with capitalist interests.